Organizational choices of banks and the effective supervision of transnational financial institutions - Tobias Tröger (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2012)
This paper outlines relatively easy to implement reforms for the supervision of transnational banking-groups in the E.U. that should not be primarily based on legal form but on the actual risk structures of the pertinent financial institutions. The proposal also aims at paying close attention to the economics of public administration and international relations in allocating competences among national and supranational supervisory bodies. Before detailing the own proposition, this paper looks into the relationship between sovereign debt and banking crises that drive regulatory reactions to the financial turmoil in the Euro area. These initiatives inter alia affirm effective prudential supervision as a pivotal element of crisis prevention. In order to arrive at a more informed idea, which determinants apart from a perceived appetite for regulatory arbitrage drive banks' organizational choices, this paper scrutinizes the merits of either a branch or subsidiary structure for the cross-border business of financial institutions. In doing so, it also considers the policy-makers perspective. The analysis shows that no one size fits all organizational structure is available and concludes that banks' choices should generally not be second-guessed, particularly because they are subject to (some) market discipline. The analysis proceeds with describing and evaluating how competences in prudential supervision are currently allocated among national and supranational supervisory authorities. In order to assess the findings the appraisal adopts insights form the economics of public administration and international relations. It argues that the supervisory architecture has to be more aligned with bureaucrats' incentives and that inefficient requirements to cooperate and share information should be reduced. Contrary to a widespread perception, shifting responsibility to a supranational authority cannot solve all the problems identified. Resting on these foundations, the last part of this paper finally sketches an alternative solution that dwells on far-reaching mutual recognition of national supervisory regimes and allocates competences in line with supervisors' incentives and the risk inherent in crossborder banking groups.
urn:nbn:de:hebis:30:3-268679
Keywords: G21; G28; H77; K22; K23; L22; 330; cross-border banking; micro-prudential supervision; consolidating supervision; banking union; subsidiaries; branches